Problem-solving Systematization: Introducing Formal Methods in Basic Education - Silva, Júlia Veiga da; Silva Junior, Braz Araujo da; Foss, Luciana; Cavalheiro, Simone André da Costa (Anais do Workshop-Escola de Informática Teórica (WEIT); 2023: Anais do VII Workshop-Escola de Informática Teórica, 2023)
Widely employed within critical systems, Formal Methods for specification and verification have gained significance in a world where computer systems continue to expand in scale. Teaching Formal Methods at the higher education level has long been accompanied by well documented challenges. However, since it is often considered an advanced subject within software engineering, it is rarely included in basic education. Targeting this unconventional audience, this paper explores a new approach to formal specification based on the systematization of problem-solving. An example of recursion elimination is presented.